2019
DOI: 10.2298/bah1904377p
|View full text |Cite
|
Sign up to set email alerts
|

Fatty acids in feed of laying hens on the production parameters and the ratio of omega-6 and omega-3 fatty acids

Abstract: Enriching table eggs with certain nutrients such as omega-3 fatty acids is an ongoing topic. Therefore, the aforementioned research was carried out with the aim of examining the possibility of feeding laying hens with ground flax seed, flax cake and flaxseed oil and their influence on the ratio of omega-6 and omega-3 fatty acids of table eggs, as well as on certain production parameters. The experiment was set up in a production facility with 192 consuming laying hens 27 weeks old. The laying… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…The results obtained in the present study are in agreement with those reported by Perić et al (2019) regarding the ratio of PUFA ω-6/ω-3 fatty acids (3.34 ± 0.62) when they included 5% flax flour in the structure of the diet. At the same time, the concentrations obtained by us in this study, when supplementing the hen's diets with 5% flaxseed meal, are similar to those obtained at an 8% flax seed level (Khan et al 2017).…”
Section: Egg Yolk Fatty Acid Contentsupporting
confidence: 93%
See 1 more Smart Citation
“…The results obtained in the present study are in agreement with those reported by Perić et al (2019) regarding the ratio of PUFA ω-6/ω-3 fatty acids (3.34 ± 0.62) when they included 5% flax flour in the structure of the diet. At the same time, the concentrations obtained by us in this study, when supplementing the hen's diets with 5% flaxseed meal, are similar to those obtained at an 8% flax seed level (Khan et al 2017).…”
Section: Egg Yolk Fatty Acid Contentsupporting
confidence: 93%
“…The α-linolenic acid concentration (C18: 3n3) in the yolk egg from experimental groups was significantly (P≤0.05) higher compared to the group C, but the highest increase, however, was recorded in the group E1. Perić et al (2019) conducted a comparative study regarding the effect of flax in several forms (flour, cake and oil) on the ratio of PUFA/SFA and ω-6/ ω-3 in eggs. The recorded results highlighted the improvement of PUFA/SFA and ω-6/ω-3 ratio when flax was included alone (5%), as well as in the mixture (10% cake and 2% oil).…”
Section: Egg Yolk Fatty Acid Contentmentioning
confidence: 99%
“…Therefore, in general, in an ideal diet the ratio between Omega-6, whose intake determines the production of molecules that stimulate inflammation (pro-inflammatory effect), and Omega- 3 with an anti-inflammatory effect should be proportionate (1-2: 1), so as to ensure a certain balance between inflammatory response and anti-inflammatory action. However, Western eating habits have shifted this balance strongly in favor of Omega-6s and, consequently, of their pro-inflammatory action, with negative effects on health 46 .…”
Section: Discussionmentioning
confidence: 99%